Tram, rail, bicycle: An unhappy triad? Rising incidence and resource consumption of tramline-associated bicycling accidents in Bern, Switzerland. (March 2021) - Gerber, Joël L.; Suppiger, Tobias; Sauter, Thomas C.; Traschitzger, Michaela; Müller, Martin; Exadaktylos, Aristomenis K.
Highlights: Tramline-associated bike accidents involve severe injuries and high resource needs. This is the first study to analyze resource consumption in the emergency department. Incidence and resource consumption have been significantly raising over time. Intoxications contribute to this problem and led to higher resource consumption. Preventive measures might effectively address and avoid many of these accidents. Abstract: Bicycle traffic and the number of accidents have been increasing in Switzerland in recent years. However, little is known about specific types of bicycling accidents – such as tramline-associated bicycling accidents (TABA) – that are potentially avoidable. This retrospective single center study of emergency department (ED) consultations analyzed TABA in the city of Bern, Switzerland. We analyzed the medical records of adult patients who presented to the ED after any bicycle accident. Patient and consultation characteristics were extracted. Incidence, important characteristics and ED resource consumption of TABA were compared with bicycle accidents that did not involve tramlines (BA). Furthermore, injury patterns and predictors of resource consumption were determined in TABA. We included a total of 298 TABA and 2351 BA over the 5.6-year study period. TABA accounted for 11.2 % of all bicycling accidents. Descriptive analysis revealed a significant increase between 2013 (lowest) and 2016 (highest) of 33.0 % in the total number of BA and 132 % in the total number of TABA. Compared to BA, TABA patients were significantly older, more often female, had a less urgent triage, and less often needed resuscitation bay treatment, hospitalization or ICU-admission (all p < 0.05). In multivariable analysis, TABA were associated with greater needs for ED resources. Most TABA injuries were to limbs (70.5 %) or the head (53.0 %), including intracranial hemorrhage (2.3 %). The radiological work-up consumed most of the resources (37.5 %), followed by physicians' work (25.8 %). Statistically significant predictors of ED resource consumption in TABA were age, triage, resuscitation bay treatment, injuries to head/clavicle, and intoxication. One out of ten patients was intoxicated. Although TABA is associated with less severe trauma than BA, it bears the risk of significant morbidity and high ED resource needs. Intoxications contribute to this problem. Our findings underline the need for preventive measures to reduce TABA in the future.